A study on the impact of types organizational culture towards job satisafction in Carsem (M) Sdn. Bhd. / Nur Shazyani Samsuri - Samsuri, Nur Shazyani (Faculty of Business and Management, 2010)
Every organization in Malaysia has their own culture environment that fits with the company and their employees. Thus, the different types of organizational culture somehow will affect the job satisfaction of employees in the organization. Due to this problem, organization should identify which types of organizational culture that can best fit with the employee’s satisfaction in the organization. The main purpose of this study is to examine and gain a better understanding of the significant relationships between the types of organizational culture towards job satisfaction among employees in Carsem (M) Sdn. Bhd. There are several types of organizational culture which include clan, adhocracy, hierarchy and market in order to determine which types of organizational culture affect the job satisfaction of employee in Carsem (M) Sdn. Bhd. Results of the present study showed that the most influential types of organizational culture that affects job satisfaction of employees is hierarchy. At the end of this study, the researcher come out with several recommendations in order to give clear vision for the organization to increase the level of job satisfaction and will give positive impacts towards employees and organization.